Current distribution control in a multi-module parallel converter system - Muhammad Amiruddin Mohamed Happy (2014)
Boost converter is a type of power converter that steps up low input DC voltage to a higher DC output voltage. However, the output voltage is influenced by the resistance of the load and controllability is non-existence. In the effort of reducing current stress to a circuit, multi modules connected in parallel are preferred. Hence, this project designs and implement controllers to regulate the output voltage and control the current distribution in the multi module parallel dc-dc boost converter. The controllers are designed for robustness and to achieve desired output voltages despite varying loads. Experiments under various operating conditions are performed and the results are presented.